2009
DOI: 10.1007/s00125-009-1323-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled diabetes increases the risk of Alzheimer’s disease: a population-based cohort study

Abstract: Aims/hypothesis Diabetes has been related to Alzheimer's disease with inconsistent findings. We aimed to clarify the association of diabetes with different dementing disorders taking into account glycaemic control, and to explore the link between glucose dysregulation and neurodegeneration. Methods A dementia-free cohort (n=1,248) aged ≥75 years was longitudinally examined to detect dementia, Alzheimer's disease and vascular dementia (VaD) cases (Diagnostic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
6
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(179 citation statements)
references
References 48 publications
9
160
6
4
Order By: Relevance
“…Although this increased incidence was quite consistent across the studies included in our review, it should be noted that more recent studies did not find a significant relation between diabetes and dementia [43], or only observed significant relations in subgroups of patients, for example in patients with undiagnosed diabetes [44], or in those patients that did not have an apolipoprotein E ε4 allele [45]. The majority of available studies subdivided dementia cases in Alzheimer's disease (AD) or vascular dementia (VaD), based on clinical diagnostic criteria.…”
Section: T2dm and Dementiasupporting
confidence: 83%
“…Although this increased incidence was quite consistent across the studies included in our review, it should be noted that more recent studies did not find a significant relation between diabetes and dementia [43], or only observed significant relations in subgroups of patients, for example in patients with undiagnosed diabetes [44], or in those patients that did not have an apolipoprotein E ε4 allele [45]. The majority of available studies subdivided dementia cases in Alzheimer's disease (AD) or vascular dementia (VaD), based on clinical diagnostic criteria.…”
Section: T2dm and Dementiasupporting
confidence: 83%
“…Most recently, Wang and colleagues, in a population-based study in Taiwan, described a 50% increase in risk of developing AD for individuals with a history of DM, in all sexes and ages, particularly in older diabetic women [43]. Among diabetic individuals, the risk of developing AD seemed to be higher in the presence of APOE ε4 allele [44] and uncontrolled DM [45].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, borderline conditions, prediabetes or impaired glucose tolerance are also related to an increased risk of AD and other dementias in very old people 75 . This relationship may be partly explained by diabetic comorbidities such as hypertension and dyslipidaemia [76][77][78] . A relationship was also found between a higher prevalence of AD in an elderly population in Finland 79 , although an analytical study of a multiethnic cohort of the elderly in the USA found no association between the metabolic syndrome and either the prevalence or incidence of AD, despite the fact that two components of the syndrome, i.e.…”
Section: Diabetes Mellitusmentioning
confidence: 99%